Canonical Wnt/β-catenin signaling activation in soft-tissue sarcomas: A comparative study of synovial sarcoma and leiomyosarcoma. (November 2018) - Briski, Laurence M; Thomas, Dafydd G; Patel, Rajiv M; Lawlor, Elizabeth R; Chugh, Rashmi; McHugh, Jonathan B; Lucas, David R
Background: Previous studies have shown that aberrant activation of the Wnt/β-catenin pathway is associated with many malignant neoplasms. This includes some soft-tissue sarcoma phenotypes, most notably synovial sarcoma, implicating potential targets for novel molecular therapies. Objective: We investigate the level of Wnt/β-catenin pathway activation present in leiomyosarcomas relative to synovial sarcomas, using expression of LEF1 and β-catenin as surrogates. Methods: Cancer outlier profile analysis was performed on messenger RNA expression datasets in Oncomine (70 synovial sarcomas, 178 leiomyosarcomas). Results for LEF1 and β-catenin messenger RNA expression were reported in terms of median-centered intensity. Separate immunohistochemical studies were performed on tissue microarrays created from 77 synovial sarcomas and 89 leiomyosarcomas using antibodies to LEF1 and β-catenin. Tumors with unequivocal strong nuclear staining involving ⩾5% of cells were interpreted as positive. Results: Cancer outlier profile analysis demonstrated a higher level of LEF1 messenger RNA expression in synovial sarcomas than in leiomyosarcomas ( p  < 0.0001), but showed no significant difference in β-catenin messenger RNA expression ( p  = 0.868). Immunohistochemistry showed most synovial sarcomas had strong nuclear expression of LEF1 (79%) and β-catenin (84%), while a small minority of leiomyosarcomas had strong nuclear expression of LEF1 (5%) and β-catenin (6%). Conclusion: These results provide further evidence that aberrant activation of the Wnt/β-catenin pathway is present in most synovial sarcomas, but not in most leiomyosarcomas. While targeting the constituents of this pathway might be effective in the treatment of synovial sarcomas, it is not likely to be an effective strategy in the treatment of leiomyosarcomas.